2022
DOI: 10.3390/brainsci12121734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Exercise in Real-World Settings on Executive Function of Typical Children and Adolescents: A Systematic Review

Abstract: Objective: The aim of this paper is to provide a systematic review of research on physical exercise in real-world settings on executive function of typical children and adolescents. Methods: The CNKI, WOS, PubMed, ScienceDirect, and SPORTDiscus databases were searched by computer. Two researchers independently screened the literature, extracted data, and evaluated the risk of bias in the included literature. Statistical analysis was performed using frequency and percentage and the χ2 test. Results: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 85 publications
1
10
0
1
Order By: Relevance
“…Planning and problem solving is a more complex skill than the other dimensions and is usually controlled by goal orientation, planning and organization, maintaining goals in working memory and monitoring behavioural performance (Chang et al, 2011; Dehaene & Changeux, 1991; Diamond, 2013). Thus, improvements in the higher structures of executive function build on the lower structures, and further improvements in planning and problem solving are only possible when inhibitory control, working memory and cognitive flexibility are effectively developed (Shi, Tang, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Planning and problem solving is a more complex skill than the other dimensions and is usually controlled by goal orientation, planning and organization, maintaining goals in working memory and monitoring behavioural performance (Chang et al, 2011; Dehaene & Changeux, 1991; Diamond, 2013). Thus, improvements in the higher structures of executive function build on the lower structures, and further improvements in planning and problem solving are only possible when inhibitory control, working memory and cognitive flexibility are effectively developed (Shi, Tang, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…shown that sequential skills yield more cognitive benefits. In addition, a systematic review by Shi, Tang, et al (2022)…”
Section: Types Of Skills Of Exercise Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the executive function is known as a multidimensional structure. Although there is ongoing debate regarding the elements of executive function, the general opinion is that executive function includes flexibility, goal setting and planning, attention and memory systems, such as working memory and inhibition control (Deer et al, 2020;Shi et al, 2022;Stillman et al, 2016;Zulherma & Suryana, 2019).…”
Section: Introductionmentioning
confidence: 99%